(untitled) (Journal of actual problems of jurisprudence, 2018)
In this article some aspects of interaction of the right state and civil society are considered. The analysis of scientific views of the considered phenomena as many-sided pair categories is given. The author’s position about conceptual distinctions of spheres of the state and civil society is stated. The principles of mutual cooperation of civil society and state in various spheres are analyzed. Public and state control, various forms of ownership are allocated as one of necessary components of the developed right state and civil society. It is noted about requirement of constructive interaction of two levels of regulation of social processes: public and state-legal. Key words: autonomy, guarantees, civil society, state, right, policy, control, freedoms.